PENGARUH SKEPTISISME PROFESIONAL AUDITOR, ETIKA PROFESI, KEAHLIAN AUDIT DAN KOMITMEN PROFESIONAL AUDITOR TERHADAP KETEPATAN PEMBERIAN OPINI OLEH AUDITOR PADA KANTOR AKUNTAN PUBLIK DI BALI - Wirasari, Ni Nengah Indah; Sunarsih, Ni Made; Dewi, Ni Putu Shinta (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2019)
The company’s need to audit company activities shows the importance of quality auditing(Accountants) services to assist in conducting audits. An accountant in carrying out an auditis required to pay attention to the audit quality, because with good audit quality it is expectedto produce financial reports that can be trusted by users of financial information. The purposeof this study was to analyze the effect of auditor professional skepticism, professional ethics,audit expertise and the auditor’s professional commitment to the accuracy of giving opinion to aPublic Accountant office in Bali.This research was conducted at all Public Accountant offices in Bali with ten officesin 2019 with the number of auditors as many as 80 people from 93 populations as samplesthrough the saturated sample method. Data collection was done by distributing questionnairesand using multiple linear regression analysis techniques.Based on the results of the analysis, the auditor’s professional skepticism, professionalethics, audit expertise and the auditor’s professional commitment contribute 32.8 percentto the accuracy of giving opinions, while the remaining 67.2 percent is influenced by othervariables not included in the research model. Through t test analysis it is known that auditorprofessional skepticism has a negative effect on the accuracy of giving opinions, professionalethics and professional commitment has a positive effect on the accuracy of giving opinionswhile audit expertise does not affect the accuracy of giving audit opinions to the Public AccountingFirm in Bali.